Effect of magnesium on the osteogenesis of normal human osteoblasts - Lu, Wei-Chen; Pringa, Ekaterini; Chou, Laisheng (Magnesium research, 2017)
Biomaterials containing magnesium are used for implants and bone regeneration. However, mechanisms underlying the biologic effects of magnesium are still largely unknown and have not been examined on normal human osteoblasts. This study was designed to test the effect of supplemented Mg concentrations between 0.5 mM and 16 mM on the osteogenic behaviors of normal human primary osteoblasts. Human primary osteoblasts were cultured in the groups with various concentrations of supplemented magnesium for various time intervals. Cell proliferation was measured using crystal violet staining. Degree of Alkaline Phosphatase (ALP) activity was measured by fluorometric assay. Expression of osteocalcin was measured by immunosorbent assay. Mineralization of cultures was determined by Alizarin Red S staining. Results showed that initial cell attachment efficiency was not affected by supplemented Mg (P > 0.05). At 21 days, proliferation rates increased in groups containing 0.5 mM-4 mM supplemented Mg and decreased in groups of supplemented 8 mM and 16 mM Mg . ALP activity and osteocalcin expression were upregulated in groups of supplemented Mg between 0.5 mM-2.0 mM (P < 0.05), but downregulated in groups with supplemented Mg concentrations of 4mM and above (P < 0.05). Cultures with 1 mM and 2 mM supplemented Mg showed upregulated mineralization activity compared to the control (P < 0.05), but downregulated in groups with supplemented Mg concentrations of 4 mM and above (P < 0.05). The present study based on an experimental design demonstrated the impact of 2 mM supplemented Mg on induced-proliferation and differentiation of normal human osteoblasts.